PENGARUH MINYAK KELAPA MURNI (VIRGIN COCONUT OIL) TERHADAP RUAM POPOK PADA BAYI - Husna Sari; Erlina Hayati; Septa Dwi Insani; Prihatini Handayani (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2022)
Babies are very sensitive to everything around them, but one of the most common skin problems in infants and children is diaper rash/rash. Diaper rash occurs due to moisture in the baby caused by the diaper overflowing due to feces and urine. VCO is virgin coconut oil that is processed at high temperatures and without the addition of chemicals. VCO contains medium chain fatty acids (MCFA), which consist of lauric acid, capric acid, caprylic acid and myristic acid. The quality of VCO is determined by lauric acid, its levels reach 45%. This study aims to determine the effect of extra virgin coconut oil on diaper rash in infants at the Pratama Kasih Ibu clinic, Deli Tua, Deli Serdang Regency in 2022. Rash 0-12 months The study was conducted using the Wilcoxon test. The results of the analysis showed a p-value of 0.009 (p < 0 0.05) for the reduction of respondents, indicating the effect of virginity. Coconut oil for skin rashes in babies. We conclude that virgin coconut oil can reduce diaper rash in babies.